Compensation for incarcerated research participants: diverse state policies suggest a new research agenda. - Smoyer, Amy B; Blankenship, Kim M; Belt, Brandis (American journal of public health, 2009)
Research with prisoners is essential to understanding the incarceration experience and creating interventions to mediate its effects on individual and community health. Policies on research involving incarcerated participants can influence the extent to which researchers are able or willing to conduct prison studies. We attempted to collect data on inmate compensation policies from all 50 states, the District of Columbia, and the Federal Bureau of Prisons. We found that 44% of these jurisdictions allow compensation for inmates who participate in research, with wide variations in terms of the clarity of and ease of access to policy information. Anecdotal data suggest considerable administrative discretion in the implementation of these policies. Further study is needed on how compensation policies are formulated and enacted and their effects on research with prisoners.
Keywords: Biomedical Research; Ethics Committees, Research; Ethics, Research; Government Regulation; Human Experimentation; Humans; Prisoners; Prisons; Public Health; Public Policy; State Government; United States